(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The article deals with the selection of geophysical methods associated with advancing the effectiveness of landslide processes, both with the description of spatial boundaries and mapping, and with the purpose of monitoring the dynamics of slip in time and forecasting.